Critical behavior and magnetic entropy change in Nd0.7Sr0.1Ba0.1Ca0.1MnO3−δ perovskite manganite. Issue 1 (January 2016) - Mtiraoui, N.; Chennabasappa, M.; Decourt, R.; Toulemonde, O.; Dhahri, J.; Oumezine, M.
Abstract: The aim of our study was to investigate the critical exponents of Nd0.7 Sr0.1 Ba0.1 Ca0.1 MnO3− δ material around its paramagnetic to ferromagnetic phase transition. Reliable critical exponents i.e. β =0.355, γ =1.329, and δ =4.867 at the critical temperature T C =117 K were refined using modified Arrott plot and Kouvel–Fisher methods. The critical exponent δ =4.760±0.129 was further separately determined from the isothermal magnetization data. Finally these critical exponents fulfill the Widom scaling relation δ =1+ γ / β . Based on these analysis, the magnetization–field–temperature ( M – H – T ) data around TC collapses into two independent curves obeying the single scaling equation M(H, ε )=| ε | β f ± ( H /| ε | β + γ ), with ε =( T − T C )/ T C is the reduced temperature. Once again, the critical exponents are confirmed by the field dependence of the magnetic entropy change relation ∆ SM | T = T C ∞ H n with n =1+( β− 1)/( β +1). The obtained critical exponents for Nd0.7 Sr0.1 Ba0.1 Ca0.1 MnO3− δ manganite are in accordance with the prediction of the 3D-Heisenberg model with short-range magnetic interactions. The temperature dependence of specific heat and magnetic entropy change Δ SM further supports second order PM–FM phase transition and shed light the A-site-disordered perovskite effect on the magnetocaloric properties.